Mycobacterium leprae deoxyribonucleic acid positivity on skin lesion of untreated leprosy patients and its route to the skin surface - Endi Novianto; Patricsia Manalu; Benny Effendi Wiryadi; Sri Linuwih Menaldi (PAGEPress Publications, 2019)
The route of transmission of leprosy is still unclear. Multiple opinions exist regarding the environmental dissemination of Mycobacterium leprae (M. leprae). This research aims to identify the positive proportion of M. leprae deoxyribonucleic acid (DNA) on skin lesion surface of untreated multibacillary leprosy patients by polymerase chain reaction (PCR), and its association with the examination result of acid-fast bacilli (AFB) in epidermis, pilosebaceous unit, and sweat glands. The M. leprae DNA sample was taken from smears of the skin lesion surface by using PCR and the skin biopsy test was done to detect AFB in epidermis, pilosebaceous unit, and sweat glands. From 28 subjects, there was 82.1% positive proportion of M. leprae DNA on the skin lesion surface of untreated multibacillary leprosy patients, where all were found in the lepromatous leprosy and borderline leprosy type. The result of AFB was positive in epidermis (71.4%), pilosebaceous unit (46.4%) and sweat glands (53.6%). We found M. leprae by using PCR technique on skin lesion surface of untreated multibacillary leprosy patients, and its route which most likely was through the epidermis.